Impact of Behavioral Factors on Investors’ Decisions in the Companies Listed in Nepal Stock Exchange - Uprety , Gaurav (KIC International Journal of Social Science and Management, 2024)
This study investigates the relationship between the behavioral characteristics (sentiment, overconfidence, overreaction and underreaction, and herd behavior) and the decisions made by investors when they are investing in businesses listed on the Nepal Stock Exchange (NEPSE). The 384 randomly chosen investors provided information via a structured questionnaire survey. Multiple regression analysis was used to achieve the study’s goal of analyzing the behavioral factors that impact investors’ decisions to invest in companies listed on the NEPSE and investigating the relationship between behavioral factors and investors’ decisions to invest in the security market. All of the behavioral elements that were chosen have a considerable impact on investment decisions, according to data analysis. Consequently, the results of the study shed light on typical investor behavior and offer recommendations for the growth of the Nepalese stock market.